Are we there yet? A systematic review and meta-analysis of the validity and reliability of automated markerless motion capture systems during jumping tasks. - Ogura, Ayane; Florio, Emily; Wileman, Taylor M.; Dennison, Louis; Psarakis, Michael (Journal of Sports Sciences, 2026)
Accurate assessment of jumping is important for sports performance and rehabilitation. While laboratory-based motion capture is considered gold-standard, markerless motion capture (MMC) systems offer an accessible alternative for field and clinical settings. However, their validity and reliability vary, warranting a comprehensive synthesis of current literature. Six databases (CINAHL, Embase, MEDLINE, Scopus, SPORTDiscus, Web of Science) were searched following PRISMA for studies comparing MMC derived kinematics, kinetics or performance with gold-standard measures during vertical or horizontal jump tasks. Twenty studies met inclusion. The meta-analysis for sagittal-plane pooled root mean square error (RMSE) values were 5.3° for hip (95% CI 2.9–7.6°), 4.4° for knee (2.9–5.9°) and 4.9° for ankle (3.9–5.9°). Frontal-plane RMSE values were 3.0° for hip (2.5–3.5°) and 7.5° for ankle (4.1–10.9°). Pooled jump-height bias was −2.9 cm (−8.1 to 2.3 cm). Between-study heterogeneity ranged from low to substantial, with wider prediction intervals for sagittal hip, frontal ankle and jump height. This review suggests that current MMC systems can achieve moderate accuracy for lower limb jump biomechanics, but performance varies widely between systems and contexts. Practitioners should consider system-specific evidence to make informed decisions regarding the suitability of a given system for their needs.